August 17th commemoration as an event promoting of healthy lifestyle in Margaasih - Tsabitah Nurulhaq; Eka Maitsa Hadyani; Riyan Ananda Nurfadilah; Awalia Latifa Mayda Ikrimah (Dedicated: Journal of Community Services (Pengabdian kepada Masyarakat), 2024)
Physical activity is an inseparable component of a healthy lifestyle. The promotion of increased physical activity can be done in various ways, one of which is by holding social activities that involve the entire community. Margaasih Village, which is located in Margaasih District, Bandung Regency, promotes this healthy lifestyle through two activities to increase physical activity, namely aerobic exercise competitions and healthy walking activities. These two activities were carried out to celebrate the anniversary of August 17. This community service aims to examine promotional activities to increase these activities through a literature review as a basis, using descriptive methods with observation as the focus of data collection. Based on the literature review and observations made, aerobic exercise competitions and healthy walking activities held by Margaasih Village to celebrate August 17 were effective as promotional media for increasing physical activity in Margaasih Village. Social activities as already implemented can be a medium for increasing public awareness of healthy lifestyles through increasing physical activity. Social activities like this would be better if they were held every month, not just during the anniversary of independence.   Abstrak Aktivitas fisik merupakan komponen yang tidak dapat dipisahkan dari pola hidup sehat. Promosi peningkatan aktivitas fisik dapat dilakukan melalui berbagai cara, salah satunya adalah dengan mengadakan kegiatan sosial yang melibatkan seluruh masyarakat. Desa Margaasih yang terletak di Kecamatan Margaasih Kabupaten Bandung melakukan promosi pola hidup sehat ini melalui dua kegiatan peningkatan aktivitas fisik, yaitu lomba senam aerobik dan kegiatan jalan sehat. Dua kegiatan tersebut dilaksanakan dalam rangka merayakan hari peringatan 17 Agustus. Pengabdian ini bertujuan untuk mengkaji kegiatan promosi peningkatan aktivitas tersebut melalui kajian literatur sebagai landasan, menggunakan metode pengabdian deksriptif dengan observasi sebagai fokus pengumpulan data. Berdasarkan kajian literatur dan observasi yang dilakukan, lomba senam aerobik dan kegiatan jalan sehat yang diadakan Desa Margaasih dalam rangka merayakan 17 Agustus efektif sebagai media promosi peningkatan aktivitas fisik di Desa Margaasih. Kegiatan sosial sebagaimana yang sudah dilaksanakan dapat menjadi media peningkatan kesadaran masyarakat akan pola hidup sehat melalui peningkatan aktivitas fisik. Kegiatan sosial-sosial seperti ini akan lebih baik bila diadakan setiap bulan tidak hanya ketika pelringatan kemerdekaan saja. Kata Kunci: hari kemerdekaan; pola hidup sehat; promosi kegiatan